ChemInform Abstract: Synthesis of Non‐natural Oligosaccharides by α‐Glucan Phosphorylase‐Catalyzed Enzymatic Glycosylations Using Analogue Substrates of α‐D‐glucose 1‐Phosphate. Issue 16 (22nd April 2014) - Kadokawa, Jun‐ichi
Abstract Review: 44 refs.